hoaks keagamaan Hoaks Keagamaan Distorsi Tafsir Al-Qur'an dan Strategi Verifikasi - Amirah Saniyah Serepa (LPPI Universitas Al-Qolam Malang, 2025)
Abstrac The phenomenon that often occurs nowadays is the rampant spread of religious hoaxes and distorted interpretations of the Qur'an in cyberspace, which have the potential to divide the community and disrupt social harmony. Religious hoaxes, in the form of false information related to teachings, figures, or interpretations of Quranic verses, spread widely through social media such as Facebook, WhatsApp, Instagram, and TikTok, as well as other online media. Distortion of Quranic interpretation occurs due to low religious literacy and minimal public knowledge about correct interpretation methods, making deviant interpretations easily accepted and disseminated. This research highlights the importance of verification strategies based on the principle of tabayyun (clarification), as taught in QS. al-Hujurat: 6, to counter religious hoaxes and maintain an authentic understanding of Islamic teachings. The research method used is a library study with primary sources in the form of socially-oriented Quranic exegeses such as Tafsir al-Misbah and Tafsir an-Nur, as well as secondary sources from previous literature and social media. A descriptive qualitative approach is used to examine the practice of verifying religious hoaxes in digital media. This research also adopts the debunking method from John Cook and Stephan Lewandowsky, which emphasises clarifying core facts, providing explicit warnings before restating hoaxes, and offering correct alternative explanations. The research results show that media and religious literacy education is very important for the community to be able to recognise and reject hoaxes as well as understand the interpretation of the Qur'an in its entirety according to its spiritual context. This research is expected to serve as a reference for preachers, academics, and policymakers in formulating effective strategies to combat religious hoaxes in the digital era. Keywords: Reliqious Hoaxes, Distortion Of Quranic Interpretation, Verification, Media And Religious Literacy.